Scenario of Water Surplus in the Narmada Basin - Devi, Rema; modi, SANDEEP (Journal of Soil and Water Conservation, 2022)
Optimal management of water resources requires a realistic assessment of the exact quantity of water available in basins and in the country. The water Resources of the Narmada basin using Water Balance Techniqthe are assessed based on normal rainfall and normal evapotranspiration data The entire basin has been divided into 71 parts on ilk; basin of similarity of soils, Potential Evapo - Transpiration and rainfall. The results of the water balance of the 71 parts are plotted graphically to show the water availability in each area. In addition to this, return flows from domestic and livestock water requirements, industrial and irrigation water demands have been taken account of for the basin and the results are discussed,